Implementasi Penerapan Perlindungan Konsumen dan Penyelesaian Sengketa Terhadap Perdagangan Pakaian Bekas di Kota Kotamobagu Sulawesi Utara - Adityo Prasetyo; Wahyu Adi Mudiparwanto (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Consumer protection is a form of protection based on law created to protect consumers and fulfill consumer rights. This research aims to implement it for consumers who feel disadvantaged and how to resolve disputes between consumers and business actors. In this research there is a normative empirical method. The results of this research state that there are losses experienced by consumers from the use of goods/or services from business actors, ultimately resulting in disputes between the two parties. Therefore, consumers do not get their rights as consumers and business actors do not carry out their business in accordance with the provisions of the applicable laws. The conclusion in this research is that even though consumers feel disadvantaged by business actors, they still get their rights as consumers. Business actors fulfill their obligations as business actors who are responsible for actions that harm consumers. Consumer protection in this case is very important to ensure justice and legal certainty for every consumer.